Chronic hyperglycemia, hypercholesterolemia, and metabolic syndrome are associated with risk of tendon injury. (4th June 2021) - Skovgaard, Dorthe; Siersma, Volkert D.; Klausen, Soren Bering; Visnes, Håvard; Haukenes, Inger; Bang, Christine W.; Bager, Peter; Grävare Silbernagel, Karin; Gaida, Jamie; Magnusson, Stig Peter; Kjaer, Michael; Couppé, Christian
Abstract : Tendon injury is a considerable problem affecting both physically active and sedentary people. The aim of this study was to examine the relationship between markers for metabolic disorders (hyperglycemia, hypercholesterolemia, and metabolic syndrome) and the risk of developing tendon injuries requiring referral to a hospital. The Copenhagen City Heart Study is a prospective study of diabetic and non‐diabetic individuals from the Danish general population with different physical activity levels. The cohort was followed for 3 years via national registers with respect to tendon injuries. Data from 5856 individuals (median age 62 years) were included. The overall incidence of tendon injury in both upper and lower extremities that required an out‐patient or in‐house visit to a hospital was ~5.7/1000 person years. Individuals with elevated HbA1c (glycated hemoglobin) even in the prediabetic range (HbA1c>5.7%) had a ~3 times higher risk of tendon injury in the lower extremities only, as compared to individuals with normal HbA1C levels. Hypercholesterolemia (total cholesterol>5 mmol/L) increased risk of tendon injury in the upper extremities by ~1.5 times, and individuals with metabolic syndrome had ~2.5 times higher risk of tendon injury in both upper and lower extremities. In conclusion, these data demonstrate for the first time in a large cohort with different physical activity levels that the indicators for metabolic syndrome are a powerful systemic determinant of tendon injury, and two of its components, hyperglycemia and hypercholesterolemia, each independently make tendons susceptible for damage and injury.